Conceptualizing intelligent system applications in the service economy: Aligning with sustainable development goals for a resilient future - Bozhuk, Svetlana; Ikramov, Murat Akramovich; Ergashxodjayeva, Shaxnoza Djasurovna; Nabieva, Nilufar Muratovna; Kurolov, Maksud Obitovich; Malenkov, Yuri; Nogovitsyn, Mikhail; Shishkin, Victor; Bakharev, Vladimir; Shishkin, Viktor I.; et al. (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the relationship between intelligent system adoption and sustainability performance in the service economy, with a focus on aligning these technologies with the United Nations Sustainable Development Goals (SDGs). A quantitative research design was employed, utilizing survey data from 200 organizations across various service sectors. The data were analyzed using descriptive statistics, correlation analysis, and multiple regression to examine the impact of intelligent system adoption on sustainability outcomes, operational efficiency, and the barriers to SDG alignment. The findings show a significant positive relationship between intelligent system adoption and sustainability performance, indicating that organizations using intelligent systems report improved environmental and operational outcomes. Additionally, intelligent system adoption is positively correlated with SDG awareness and integration, while barriers such as financial constraints and lack of expertise negatively impact sustainability efforts. The study concludes that intelligent systems can play a critical role in driving sustainable business practices and enhancing organizational efficiency. However, overcoming barriers to SDG alignment requires targeted policy interventions and financial support. These findings provide practical insights for organizations seeking to leverage intelligent systems for sustainability and contribute to the broader discourse on the role of digital technologies in achieving global sustainability goals.